Optimization of heat and relative humidity conditions to reduce Escherichia coli O157:H7 contamination and maximize the germination of radish seeds. (June 2016) - Song, M.K.; Kim, H.W.; Rhee, M.S.
Abstract: We previously reported that a combination of heat and relative humidity (RH) had a marked bactericidal effect on Escherichia coli O157:H7 on radish seeds. Here, response surface methodology with a Box-Behnken design was used to build a model to predict reductions in E. coli O157:H7 populations based on three independent variables: heating temperature (55 °C, 60 °C, or 65 °C), RH (40%, 60%, and 80%), and holding time (8, 15, or 22 h). Optimum treatment conditions were selected using a desirability function. The predictive model for microbial reduction had a high regression coefficient (R 2 = 0.97), and the accuracy of the model was verified using validation data (R 2 = 0.95). Among the three variables examined, heating temperature ( P < 0.0001) and RH ( P = 0.004) were the most significant in terms of bacterial reduction and seed germination, respectively. The optimum conditions for microbial reduction (6.6 log reduction) determined by ridge analysis were as follows: 64.5 °C and 63.2% RH for 17.7 h. However, when both microbial reduction and germination rate were taken into consideration, the desirability function yielded optimal conditions of 65 °C and 40% RH for 8 h (6.6 log reduction in the bacterial population; 94.4% of seeds germinated). This study provides comprehensive data that improve our understanding of the effects of heating temperature, RH, and holding time on the E. coli O157:H7 population on radish seeds. Radish seeds can be exposed to these conditions before sprouting, which greatly increases the microbiological safety of the products. Highlights: Combined use of heat and relative humidity (RH) inactivated pathogens on the seeds. Response surface methodology was used to establish a predictive model (R 2 = 0.97). The optimum conditions were 65 °C, 40% RH, for 8 h (6.6 log reduction). The model and optimized conditions will be of practical use to the sprout industry.